2016
DOI: 10.1002/1873-3468.12426
|View full text |Cite
|
Sign up to set email alerts
|

Heparin promotes fibril formation by the N‐terminal fragment of amyloidogenic apolipoprotein A‐I

Abstract: Glycosaminoglycans are known to be associated with extracellular amyloid deposits of various amyloidogenic proteins. In this study, we found that the glycosaminoglycan heparin greatly accelerates the elongation step in fibril formation by the N-terminal 1-83 fragment of human apolipoprotein A-I (apoA-I), especially in the amyloidogenic W50R variant. Using fragment peptides, we demonstrate that heparin significantly promotes β-transition and fibril formation of the highly amyloidogenic region spanning residues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…In a cellular environment, membrane lipid compositions as well as extracellular matrix components are thought to mediate formation and deposition of amyloid fibrils in many amyloidogenic proteins 59 61 . Indeed, glycosaminoglycans such as heparin and heparan sulfate were shown to play critical roles in formation and cellular interaction of apoA-I amyloid fibrils 26 , 62 64 . In addition, it has been demonstrated that membrane binding strongly inhibits fibril formation by the N-terminal fragments of apoA-I through entrapping the protein in a stable α-helical structure 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cellular environment, membrane lipid compositions as well as extracellular matrix components are thought to mediate formation and deposition of amyloid fibrils in many amyloidogenic proteins 59 61 . Indeed, glycosaminoglycans such as heparin and heparan sulfate were shown to play critical roles in formation and cellular interaction of apoA-I amyloid fibrils 26 , 62 64 . In addition, it has been demonstrated that membrane binding strongly inhibits fibril formation by the N-terminal fragments of apoA-I through entrapping the protein in a stable α-helical structure 27 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is known that stabilization of the α-helical structure of proteins generates a kinetic trap in transition to β-strand structure, thereby inhibiting the aggregation and fibril formation 21 23 . In apoA-I, the N-terminal amino acid 1‒83 or 1‒93 fragments that are predominantly a random coil structure in solution have a strong propensity to form amyloid fibrils 11 , 24 26 . However, a lipid environment promotes the transition to the α-helical structure, thereby preventing the β-aggregation and fibril formation of the proteins 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…The W50R mutation, known as an amyloidogenic mutation in apoA-I 57, 58 , places the strongly basic arginine residue into the nonpolar face of the amphipathic α-helix in residues 44–65 (Fig. 5C left), leading to destabilization of the helical structure.…”
Section: Resultsmentioning
confidence: 99%
“…S7). The apoA-I 44–65 peptide was synthesized by the solid-phase method with Fmoc chemistry 58, 60 . These apoA-I variants and peptide were dialyzed from 6 M guanidine hydrochloride solution into PBS before use.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the disruptive presence of a positive charge in replacement of the aromatic Trp is detected in our experimental design by an increased yield in the Bis-ANS binding and minor change in the near UV spectra, together with the detection of stronger binding to heparin at acidic pH. It is worth mentioning that the N-terminal 1–83 fragment of W50R variant was shown to participate in heparin-mediated fibril formation [39].
Fig 9. Locations of amyloidogenic mutations W50R and L60R in the structure of apoA-IThe structure was obtained by the PyMOL Molecular Graphics System, Version 2.0 (Schrödinger, LLC), from the X-ray crystal structure of Δ(185-243) apoA-I (PDB ID 3R2P).
…”
Section: Discussionmentioning
confidence: 99%